Oxidation of sitosterol and transport of its 7-oxygenated products from different tissues in humans and ApoE knockout mice. Issue 169 (May 2017) - Schött, Hans-Frieder; Baumgartner, Sabine; Husche, Constanze; Luister, Alexandra; Friedrichs, Silvia; Miller, Charlotte M.; McCarthy, Florence O.; Plat, Jogchum; Laufs, Ulrich; Weingärtner, Oliver; Lütjohann, Dieter
Highlights: Sitosterol is preferably oxidized in the human and mouse circulation. 7β-OH-sitosterol is preferably transported out of peripheral tissue. Oxidation of sitosterol might control its concentration in peripheral tissue. Preferred oxidation and product transport might be sitosterol clearance mechanism. Abstract: The most common phytosterols in the human diet are sitosterol and campesterol, which originate exclusively from plant derived food. These phytosterols are taken up by NPC1L1 transport from the intestine into the enterocytes together with cholesterol and other xenosterols. Phytosterols are selectively pumped back from the enterocytes into the intestinal lumen and on the liver site from hepatocytes into bile by heterodimeric ABCG5/G8 transporters. Like cholesterol, both phytosterols are prone to ring and side chain oxidation. It could be shown that oxyphytosterols, found in atherosclerotic tissue, are most likely of in situ oxidation (Schött et al.; Biochem. Biophys. Res. Commun. 2014 Apr 11;446(3):805-10). However, up to now, the entire mechanism of phytosterol oxidation is not clearly understood. Here, we provide further information about the oxidation of sitosterol and the transport of its oxidation products out of tissue. Our survey includes data of 104 severe aortic stenosis patients that underwent an elective aortic valve cusp replacement. We studied their phytosterol concentrations, as well as absolute and substrate corrected oxyphytosterol levels in plasma and valve cusp tissue. In addition, we also examined phytosterol and oxyphytosterol concentrations in plasma and tissues (from brain and liver) of 10 male ApoE knockout mice. The ratio of 7-oxygenated-sitosterol-to-sitosterol exceeds the ratio for 7-oxygenated-campesterol-to-campesterol in plasma and tissue of both humans and mice. This finding indicates that sitosterol is oxidized to a higher amount than campesterol and that a selective oxidative mechanism might exist which can differentiate between certain phytosterols. Secondly, the concentrations of oxyphytosterols found in plasma and tissue support the idea that oxysitosterols are preferably transported out of individual tissues. Selective oxidation of sitosterol and preferred transport of sitosterol oxidation products out of tissue seem to be a metabolic pathway of forced sitosterol clearance from tissue compartments.